Gaya Bahasa dalam Lirik Lagu Kepada Noor-Panji Sakti - Amrullah, Asyraf; Shadiqin, Muhammad Irsyad Ash (Jurnal Bahasa dan Sastra, 2024)
This research aims to examine the authentic meaning of the lyrics of the song "Kepada Noor" by Panji Sakti through a mixed analysis of listening and viewing. The lyrics are very deep and have messages from both religious and social aspects. This research aims to find out, describe and conclude what the appeal of a song is among teenagers and to find out the message contained in the lyrics of the song "to Noor". The research method used is a qualitative method and a deductive way of thinking, namely a way of thinking from general to specific. This research shows that of every song that young people or teenagers listen to, they choose songs that are relaxing and represent their feelings. This song also has a history of its creation which was adapted from a quite famous poem by Moch Syarip Hidayat. The implication of the findings of this research is that there is a growing sense of enthusiasm and appreciation for every song you listen to. The existence of the song "Kepada Noor" at least opens up some knowledge that songs are not just heard but understood the message and meaning contained in them.